2004
DOI: 10.1021/jp047777p
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surface Anchoring Groups (Carboxylate vs Phosphonate) in Ruthenium-Complex-Sensitized TiO2 on Visible Light Reactivity in Aqueous Suspensions

Abstract: This study compares the visible light reactivities and properties of two sensitized Pt/TiO 2 photocatalysts (Pt/ TiO 2 /RuL 3 ) on which ruthenium bipyridyl complexes (RuL 3 ) are anchored through carboxylic (c-RuL 3 ) or phosphonic (p-RuL 3 ) acid groups. The photoreductive dechlorination of CCl 4 and trichloroacetate (TCA) and the hydrogen production in aqueous suspensions were used as probe reactions for the visible light reactivity. The molar absorptivity of p-RuL 3 was lower than that of c-RuL 3 , but Pt/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
237
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 286 publications
(248 citation statements)
references
References 44 publications
10
237
1
Order By: Relevance
“…It should be noted that a large effect of anchor group on molecular conductance was pointed out in a previous theoretical study. 84 These anchoring groups differ in both the binding strength to surface 27,[48][49][50][51][52][53] and electronic structure. 52, 54 Stronger binding of phosphonate to TiO 2 than the carboxylate anchoring group has been observed in experiments 27,[48][49][50][51][52][53] and confirmed in computational modeling.…”
Section: Ph Dependence Of Photophysicsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that a large effect of anchor group on molecular conductance was pointed out in a previous theoretical study. 84 These anchoring groups differ in both the binding strength to surface 27,[48][49][50][51][52][53] and electronic structure. 52, 54 Stronger binding of phosphonate to TiO 2 than the carboxylate anchoring group has been observed in experiments 27,[48][49][50][51][52][53] and confirmed in computational modeling.…”
Section: Ph Dependence Of Photophysicsmentioning
confidence: 99%
“…84 These anchoring groups differ in both the binding strength to surface 27,[48][49][50][51][52][53] and electronic structure. 52, 54 Stronger binding of phosphonate to TiO 2 than the carboxylate anchoring group has been observed in experiments 27,[48][49][50][51][52][53] and confirmed in computational modeling. 54 A recent periodic hybrid HF-DFT study of HPO 3 H 2 and HCOOH on anatase TiO 2 (101) surface has found the binding energy in the former to be ∼20 kcal/mol larger.…”
Section: Ph Dependence Of Photophysicsmentioning
confidence: 99%
“…As a mean to achieve this goal, semiconductor photocatalysts have been extensively studied. In particular, a variety of visible light-active photocatalyts [2][3][4][5][6] including CdS [7][8][9][10][11][12][13] have been studied. In terms of the band gap magnitude and the position of band edges, CdS is ideally suited for photocatalytic water splitting but it is not effective at all unless suitable electron donors (EDs) are present.…”
Section: Introductionmentioning
confidence: 99%
“…There remain significant interests in designing sensitizers with phosphonate anchoring groups because they have been shown to bind more strongly with metal oxide substrates than carboxylate and are expected to lead to better long-term cell stability. 8,[11][12][13][14][15][16] The incident photon-to-current conversion efficiency was found to be near unity in RuN3-sensitized TiO 2 solar cells, 2,10 and the high efficiency has been attributed to an ultrafast electron injection and a much slower charge recombination that happens on the microsecond to millisecond time scales. [17][18][19] The injection kinetics has been shown to be biphasic, consisting of a primary <100 fs component and slower components on a few to tens of picosecond time scales.…”
Section: Introductionmentioning
confidence: 99%